PENGENALAN PENGUKURAN SUDUT (ANGLE) DAN APLIKASINYA DI KELAS V SEKOLAH DASAR (SD N 5 KERAMAS – BLAHBATUH) - N. M Asih; L. P. Suciptawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2014)
The aim of learning the introduction of measurement angle (acute angle, obtuse angle and privileged corner) at SDN5 Keramas Blahbatuh, can be understood by all students. Application in everyday life of objects that have angles can also be understood and mentioned by the students, hence increased students increase learning outcomes. Learning results show that the score of the average pre-test 60.16 increased after learning that occur spost-test average of 83.58. Test results do not accept H0 hypothesis, namely that the effect of treatment after a given learning, seen from the Evaluate that indicates 0.094. This means the application of learning and angle measurement application runs fine and successfully for student learning outcomes.Keywords: Measurement ofangle, Classroom action research, question and answer method, the inquirymethod.